‘Paul and "Prepositional Metaphysics": A Brief Response to George H. van Kooten’ - Kugler, Chris (New Testament studies, 2025)
George H. van Kooten has recently argued that Paul’s use of ‘from him/whom’ language with reference to God the father in Romans 11.36 and 1 Corinthians 8.6, in light of the semi-technical use of this prepositional formula in the Greek metaphysical traditions, indicates that God/the father is a material cause. And this coheres, so van Kooten further argues, with other indications that Paul’s metaphysic is fundamentally Stoic. This article focuses on van Kooten’s claim that Paul’s use of ‘from him/whom’ language with reference to God the father indicates that the latter is, for Paul, a material cause. In this regard, van Kooten has mistranslated and misconstrued key data both in the ancient metaphysical traditions and in Paul and also committed the genealogical fallacy: taking individual lexemes, formulas and/or tropes to suggest that the entire metaphysical construct of one of the earlier philosophical schools (in this case, Stoicism) from which they derive should wholly govern their interpretation in a much later and different text.